Lichtenstein Versus Total Extraperitoneal Patch Plasty Versus Transabdominal Patch Plasty Technique for Primary Unilateral Inguinal Hernia Repair: A Registry-based, Propensity Score-matched Comparison of 57, 906 Patients. Issue 2 (February 2019) - Köckerling, Ferdinand; Bittner, Reinhard; Kofler, Michael; Mayer, Franz; Adolf, Daniela; Kuthe, Andreas; Weyhe, Dirk
Abstract : Objective: Outcome comparison of the Lichtenstein, total extraperitoneal patch plasty (TEP), and transabdominal patch plasty (TAPP) techniques for primary unilateral inguinal hernia repair. Background: For comparison of these techniques the number of cases included in meta-analyses of randomized controlled trials is limited. There is therefore an urgent need for more comparative data. Methods: In total, 57, 906 patients with a primary unilateral inguinal hernia and 1-year follow up from the Herniamed Registry were selected between September 1, 2009 and February 1, 2015. Using propensity score matching, 12, 564 matched pairs were formed for comparison of Lichtenstein versus TEP, 16, 375 for Lichtenstein versus TAPP, and 14, 426 for TEP versus TAPP. Results: Comparison of Lichtenstein versus TEP revealed disadvantages for the Lichtenstein operation with regard to the postoperative complications (3.4% vs 1.7%; P < 0.001), complication-related reoperations (1.1% vs 0.8%; P = 0.008), pain at rest (5.2% vs 4.3%; P = 0.003), and pain on exertion (10.6% vs 7.7%; P < 0.001). TEP had disadvantages in terms of the intraoperative complications (0.9% vs 1.2%; P = 0.035). Likewise, comparison of Lichtenstein versus TAPP showed disadvantages for the Lichtenstein operation with regard to the postoperative complications (3.8% vs 3.3%; P = 0.029), complication-related reoperations (1.2% vs 0.9%; P = 0.019), pain at rest (5% vs 4.5%; P = 0.029), and on exertion (10.2% vs 7.8%; P < 0.001). Conclusions: TEP and TAPP were found to have advantages over the Lichtenstein operation.